2020
DOI: 10.7224/1537-2073.2020-014
|View full text |Cite
|
Sign up to set email alerts
|

Falls in People with Multiple Sclerosis

Abstract: Falls are highly prevalent for people with Multiple Sclerosis (MS) and result in a range of negative consequences such as injury, activity curtailment, reduced quality of life, increased need for care and time off work. This narrative review aims to summarise key literature and to discuss future work needed in the area of falls prevention for people with MS. The incidence of falls is estimated to be over 50%; similar to the rate of falls in adults over 80 years. The consequences of falls are considerable as ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 94 publications
(110 reference statements)
1
26
0
Order By: Relevance
“…Consequentially, approximately 75–90% of PwMS experience mobility issues [ 3 ] and PwMS fall at a higher rate and more often than those aging without neurologic impairment [ 4 ]. Over half of PwMS fall in any 6-month period [ 5 ], with many experiencing repeated falls and falls-related injury [ 6 ]. Falls can intensify already existing fear of falling [ 7 ], decrease physical activity [ 6 ], and reduce quality of life [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequentially, approximately 75–90% of PwMS experience mobility issues [ 3 ] and PwMS fall at a higher rate and more often than those aging without neurologic impairment [ 4 ]. Over half of PwMS fall in any 6-month period [ 5 ], with many experiencing repeated falls and falls-related injury [ 6 ]. Falls can intensify already existing fear of falling [ 7 ], decrease physical activity [ 6 ], and reduce quality of life [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over half of PwMS fall in any 6-month period [ 5 ], with many experiencing repeated falls and falls-related injury [ 6 ]. Falls can intensify already existing fear of falling [ 7 ], decrease physical activity [ 6 ], and reduce quality of life [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has explored the burden of disability among patients with neurological conditions [ 4 - 6 ]. Older adults living with neurological disorders are at a significantly higher risk of falls compared to healthy older adults [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, motor function deficits make common activities challenging for stroke survivors, such as reaching, grasping, and holding onto household objects [ 5 ]. Similar functional impairments have been observed in people with MS. Coote et al [ 6 ] reported that over a 6-month period, 71% of older adults with MS sustained a fall compared to 41% of age-matched healthy controls. Individuals with MS who experienced a fall were much more likely to sustain serious injury [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation